2018
DOI: 10.1063/1.5022454
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of emission of InGaN/GaN multiple-quantum-well nanorods by coupling to Au-nanoparticle plasmons

Abstract: We demonstrate the enhancement of emission of InGaN/GaN multiple-quantum-well nanorods by nearly a factor of 2 by coupling them to localized surface plasmons of Au nano-particles (NPs). The Au NPs are fabricated in situ on the nanorods using a Ni/SiO2/Au/SiNx compound functional layer. This layer serves as a combination dry-etch mask for fabricating the nanorods and the Au NPs, as well as providing isolation necessary to prevent fluorescence quenching. Time-resolved photoluminescence measurements confirm that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…The LSPR produce strong evanescent electrical field which can enhance light absorption or light emission in adjacent semiconductor or chemical or biological environment. This is why LSPR in metallic nanoparticles in last two decades have been applying to enhance absorption in conventional or organic photovoltaics [1][2][3] or to enhance light emission in light-emitting device 4,5 . Strong evanescent field in metallic nanoparticles can enhance the emission in weakly fluorescent biomolecules such that it also has been applying in biological sensing [6][7][8][9] .…”
mentioning
confidence: 99%
“…The LSPR produce strong evanescent electrical field which can enhance light absorption or light emission in adjacent semiconductor or chemical or biological environment. This is why LSPR in metallic nanoparticles in last two decades have been applying to enhance absorption in conventional or organic photovoltaics [1][2][3] or to enhance light emission in light-emitting device 4,5 . Strong evanescent field in metallic nanoparticles can enhance the emission in weakly fluorescent biomolecules such that it also has been applying in biological sensing [6][7][8][9] .…”
mentioning
confidence: 99%
“…Young S [24][25][26][27] team used Au nanoparticles improved ZnO UV photodetectors, obtained responsivity and I ph /I dark reached 14.8 mA/W, 1320, respectively. Xing J [28] coupled InGaN/GaN multiple quantum well nanorods with localized surface plasmons of gold nanoparticles, and time-resolved photoluminescence measurements confirmed that the emission enhancement originated from the coupling. Zhai S Q [29] demonstrated a normal-incidence quantum cascade detector excited by surface plasmon resonance using Au 2D hole arrays, and the results showed that Au 2D hole arrays resulted in enhanced quantum efficiency at most measurement temperatures, with a quantum efficiency enhanced 69% at 140 K. Dixit T [30] reported a device using Au nanoparticles sandwiched between two ZnO layers, which is suitable for UV-A, UV-B and UV-C detection, the device exhibits a high UV-to-visible rejection ratio of 1.32×10 3 and a UV-to-NIR rejection ratio of 8.79×10 3 , with a photoresponsivity of 10.64 A/W (λ = 315 nm).…”
Section: Introductionmentioning
confidence: 91%
“…It is well known that another surface plasmon can be induced when the confined carriers in QWs resonate with the oscillating electrons in the metal within a near-field distance . SPR excitation by the QW–metal coupling has been utilized to enhance the quantum efficiencies of InGaN-based LEDs, as well as to detect localized refractive index variation . In the setup for Figure b, a similar plasmonic effect could be prompted considering the fact that the abundant electrons in the multiple QWs are only ∼1 nm from the Au NPs.…”
mentioning
confidence: 99%